Rational design of a genome‐based insulated system in Escherichia coli facilitates heterologous uricase expression for hyperuricemia treatment. Issue 2 (21st November 2022) - He, Lina; Tang, Wei; Huang, Ling; Zhou, Wei; Huang, Shaojia; Zou, Linxuan; Yuan, Lisha; Men, Dong; Chen, Shiyun; Hu, Yangbo
Abstract: Hyperuricemia is a prevalent disease worldwide that is characterized by elevated urate levels in the blood owing to purine metabolic disorders, which can result in gout and comorbidities. To facilitate the treatment of hyperuricemia through the uricolysis, we engineered a probiotic Escherichia coli Nissle 1917 (EcN) named EcN C6 by inserting an FtsP‐uricase cassette into an "insulated site" located between the uspG and ahpF genes. Expression of FtsP‐uricase in this insulated region did not influence the probiotic properties or global gene transcription of EcN but strongly increased the enzymatic activity for urate degeneration, suggesting that the genome‐based insulated system is an ideal strategy for EcN modification. Oral administration of EcN C6 successfully alleviated hyperuricemia, related symptoms and gut microbiota in a purine‐rich food‐induced hyperuricemia rat model and a uox ‐knockout mouse model. Together, our study provides an insulated site for heterologous gene expression in EcN strain and a recombinant EcN C6 strain as a safe and effective therapeutic candidate for hyperuricemia treatment.